Perancangan Sistem Promosi Olahan Hasil laut Menggunakan OpenCart pada UMKM di Kabupaten Tanjungbalai - Sitorus, Nazwa Yupada Putri; Annas, Firdaus; Naufal, M. Hafizh (JOVISHE : Journal of Visionary Sharia Economy, 2024)
This article discusses the design of an e-commerce-based promotion system using the OpenCart platform to support seafood processing MSMEs in Tanjungbalai Regency. This study aims to increase product visibility, expand market reach, and strengthen the competitiveness of processed products such as salted fish and anchovies, which have so far been promoted through traditional methods. The use of conventional promotion methods has been proven to limit MSME market access, so new, more effective strategies are needed to support their business growth. This study uses the Research and Development (R&D) methodology with the RAD (Rapid Application Development) development model consisting of three stages, namely the Requirements Planning, Design Workshop, Implementations stages. The results of the study show that the OpenCart platform is able to increase promotional efficiency by presenting product catalogs digitally, facilitating consumer access, and opening up opportunities for online transactions. The impact of implementing this platform includes increasing product visibility, expanding the market outside the region, and increasing competitiveness at the national and international levels. In addition, this study also provides implications for the development of human resources in MSMEs, especially in mastering information technology and digital marketing strategies. Thus, this article provides guidance for MSMEs to optimally utilize e-commerce in supporting local economic growth and improving business sustainability in the digital era.